"Magister ludi": mito e erotismo em Horácio - Bruno Francisco dos Santos Maciel (2021)
This research proposes to reconsider the idea of eroticism in Horace, an element of his poems often neglected, underestimated or marginalized by his critical fortune. From the exploration of the ambiguity of the notion of ludus (“play”) and, in particular, of its erotic dimension, an overall reading of the Horatian sermo (Satires and Epistles) and lyric is undertaken. Conceived much less as a “joke” than as a kind of writing practice in constant dialogue with the “extratextual world”, ludus can unfold erotically, especially based on its most fundamental idea of movement and dynamism related to the scenic game, in two very concrete aspects: wordplays (ludi) and erotic dramas (ludi). The first in dialogue with the so-called atomology of Lucretius, the second with Plato’s eroticism. In these terms, the erotic dimension of ludus plays a crucial role in the metapoetic and reflexive construction of “original” (poly)myths of poet and poetry in Horace. In a close dialogue with the incessant circulation and exchange of roles of the Horatian fiction’s characters within an erotic relationship between erastés (amator) and erômenos (amatus), the wordplays (ludi), for example, between Lydia, Lyde and ludia, callida and calida, tempora and tempora, Maecenas and Camena, ira and ira, principe and incipe, erus and (h)eres are significantly productive to (re)consider the poet’s literary relationship with historical characters such as Augustus or Maecenas and still with Greek poetry, ironically moving, destabilizing and reversing their places of power, and rebounding even on the issue of imitatio (and aemulatio). Finally, an interpretation is proposed that, mobilizing traditional mythological figures such as Jupiter, Eros, Venus and Mercury, seeks to place eroticism at the center of the grammar of Horace’s poetics, read as an erotic plot of a literary cosmos, which is subdivided in a poetic homeland, house and ego.